Erfahrbares Programmieren durch den zielgerichten Einsatz von Flugdrohnen im Informatikunterricht - Raphael Zender; Alrik Dittrich; Julius Höfler; Ulrike Lucke (FernUniversität Hagen, 2015)
Today, teaching on fundamental programming skills is one of the essential IT-related topics in schools. This trend is brought forward by simple development environments like Scratch. Those abstract from detailed programming concepts in terms of graphical building blocks. Exotic runtime platforms like robots further increase the attractiveness. The solution "ScratchDrone" provides quadrocopters as an innovative new platform to run Scratch programs. The modular system architecture of ScratchDrone allows children to program on multiple layers of abstraction depending on their individual learning progress. The combination of a multi-layer didactical model, the movement in 3D space, as well as the natural human fascination for flying results in a high learning motivation for young programmers.